Zonação, variabilidade e inter-relação da fauna de peixes de dois reservatórios do rio Iguaçu, Paraná, Brasil. - Baumgartner, Dirceu (2010)
This study aimed to evaluate the formation of longitudinal and vertical gradients (zonation) of fish fauna and limnological variables, as well as assess the variability of abundance and interrelation of fish species from the Salto Osório (run-of-river) and Salto Santiago (water storage) reservoirs, both positioned in the central region of the Iguaçu River reservoirs cascade. For this, samples were taken monthly during the period from July 2003 to June 2005, and bimonthly from July 2005 to May 2006 for fish, and bimonthly from July 2003 to May 2006 for limnological variables. Data were obtained from three sampling stations in the longitudinal axis (herein named riverine, transitional and lacustrine zones) and two sampling stations in the vertical axis (surface and bottom). This study was divided into two chapters, the first entitled "Effect of dam operation on formation of longitudinal and vertical gradients in reservoirs of the Iguaçu River, Paraná, Brazil" aimed to evaluate if reservoirs with different operation systems presented differences in limnological and ichthyological variables according to vertical and longitudinal directions of the reservoirs. Another objective was to verify if there were increasing differences in the longitudinal direction of the reservoir, which would indicate formation of gradients. In the second chapter, entitled "Variability and inter-relation of the ichthyofauna from the Salto Osorio (run-of-river) and Salto Santiago (water storage) reservoirs, Iguaçu River, Paraná, Brazil", the variability (by the coefficient of variation) of the species abundance was estimated, which was correlated with hydrological variables to observe possible influences of these variables on the regulatory mechanisms of the assemblage. Inter-relation was assessed from the dominant eigenvalue of the error covariance matrix of first-order autoregressive models of species abundances in the reservoirs. We tried from these metrics to identify whether reservoirs with different operations types had different behaviors.